System dynamics for engineering students concepts and applications - Lobontiu, Nicolae (Academic Press, 2010)
"System Dynamics is an engineering discipline in which students learn how to create and analyze mathematical models of dynamic mechanical, electrical/electromagnetic, thermal and fluid/pneumatic systems with the practical goal of using this knowledge to design and test various real-world systems before they are built, thus realizing significant cost savings. "System Dynamics for Engineering Students" by Nicolae Lobontiu, takes the classical approach to system dynamics, rearranges it into a more logical teaching progression, provides a more balanced coverage of the main field systems(mechanical, electrical/electromagnetic, thermal and fluid/pneumatic), and is the first system dynamics textbook to include extensive examples from the relatively new application areas of microelectromechanical systems (MEMS) and compliant (flexible) mechanical devices. Written by an established author with extensive teaching and research experience in the field of MEMS/NEMS, this book also provides unique coverage of couple-field problems and offers more ancillary instructor support than any other system dynamics text."